Pengaruh Self-Efficacy, Relation Support, dan Entrepreneurship Education Terhadap Entrepreneurial Intention Mahasiswa S1 Manajemen Angkatan 2022 FEB UNEJ - Triya Anggun Prastika Sari (Fakultas Ekonomi dan Bisnis, 2026)
Unemployment remains one of the major challenges in Indonesia; therefore, efforts are needed to foster entrepreneurship by enhancing entrepreneurial intentions among university students. This study aims to examine the effect of self- efficacy, relation support, and entrepreneurship education on entrepreneurial intention among undergraduate students of the Management Study Program, Class of 2022, Faculty of Economics and Business, University of Jember. The population of this study consisted of 257 active undergraduate Management students from the Class of 2022 at the Faculty of Economics and Business, University of Jember. The sample was determined using a simple random sampling method based on the Slovin formula with a 5% margin of error, resulting in 153 respondents. This research employed a quantitative approach, utilizing primary data collected through questionnaires and secondary data obtained from relevant journals, books, and official websites. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that self-efficacy has a positive and significant effect on entrepreneurial intention among undergraduate Management students of the Class of 2022 at the Faculty of Economics and Business, University of Jember. In addition, relation support has a positive and significant effect on entrepreneurial intention. Furthermore, entrepreneurship education also has a positive and significant effect on entrepreneurial intention among undergraduate Management students of the Class of 2022 at the Faculty of Economics and Business, University of Jember.
Finalisasi 2 Juli 2026_Yudi
Keywords: entrepreneurship; self-efficacy; relation support; entrepreneurship education; entrepreneurial intention